Perovskite solar cell structure, preparation method and cell
By designing multi-layer structure and interface modification layers in perovskite solar cells, the problem of poor stability of perovskite materials is solved, and the stability and photoelectric conversion efficiency of perovskite solar cells are improved.
Patent Information
- Application Number
- CN202411393796.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-03
AI Technical Summary
Perovskite solar cells have attracted attention for their low cost and excellent photoelectric properties, but due to their low material decomposition energy and easy diffusion of ions, they lead to poor battery stability and reduced initial performance.
A perovskite solar cell structure is designed, including a combination of conductive glass layer, hole transport layer, multi-layer interface modification layer, electron transport layer and metal electrode layer, fixed FA+ cations through hydrogen bonds and induce Cl-doping. , adjust the interface between perovskite and carbon 60 membrane layer, use 2-thiophene ethylamine chloride for passivation, and enhance charge transfer and energy band matching.
有效提升了钙钛矿太阳能电池的稳定性和光电转换效率,减少了界面缺陷态,延长了钙钛矿膜层的稳定性和器件性能。
Smart Images

Figure CN119255620A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photovoltaic cells, and in particular to a perovskite solar cell structure, a preparation method and a cell. Background Art
[0002] With the continuous development of solar cells, perovskite solar cells have attracted much attention internationally due to their outstanding advantages such as low cost, easy preparation and excellent photoelectric properties. Perovskite is also considered to be the next generation of low-cost and high-efficiency photovoltaic materials with the most application prospects.
[0003] However, the decomposition energy of the perovskite material itself is low, and ions are easy to diffuse. Due to the ionic bonding characteristics of perovskite, ions are easy to migrate. The existing perovskite solar cell structure will cause the initial efficiency to decrease when the battery works in the sun for a long time, and the battery stability is poor.
[0004] Therefore, how to design a perovskite solar cell structure to improve the stability of the perovskite solar cell has become a technical problem that needs to be urgently solved by those skilled in the art. Summary of the invention
[0005] The present invention provides a perovskite solar cell structure, a preparation method and a battery to improve the structural stability of the perovskite solar cell.
[0006] In order to solve the above technical problems, an embodiment of the present invention provides a perovskite solar cell structure, including: a conductive glass layer, a hole transport layer, a first interface modification layer, a power generation layer, a second interface modification layer, a third interface modification layer, a first electron transport layer, a second electron transport layer, a conductive layer, and a metal electrode layer arranged in sequence from bottom to top.
[0007] The conductive glass layer is disposed on one side of the hole transport layer, and the first interface modification layer is disposed on the side of the hole transport layer away from the conductive glass layer.
[0008] One side of the power generation layer is the first interface modification layer, and the second interface modification layer is disposed on the side of the power generation layer away from the first interface modification layer.
[0009] One side of the third interface modification layer is the second interface modification layer, and the first electron transport layer is disposed on the side of the third interface modification layer away from the second interface modification layer.
[0010] The first electron transport layer is disposed on one side of the second electron transport layer, and the conductive layer is disposed on the side of the second electron transport layer away from the first electron transport layer.
[0011] The metal electrode layer is disposed on a side of the conductive layer away from the second electron transport layer.
[0012] The first interface modification layer and the second interface modification layer are both prepared from dihydrochlorinated piperazine.
[0013] Furthermore, the thickness of the first interface modification layer and the second interface modification layer is 10-30 nm.
[0014] Furthermore, the power generation layer is composed of Cs 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 Prepared.
[0015] Furthermore, the thickness of the power generation layer is 300-500 nm.
[0016] Furthermore, the power generation layer is prepared from MAPbI3 or FAPbI3.
[0017] Furthermore, the third interface modification layer is prepared from 2-thiopheneethylamine chloride.
[0018] Furthermore, the thickness of the third interface modification layer is 10-30 nm.
[0019] Another embodiment of the present invention provides a method for preparing a perovskite solar cell, which is applied to the perovskite solar cell structure as described above, comprising:
[0020] A NiMgLiO film layer is deposited on the conductive glass layer by magnetron sputtering as a hole transport layer.
[0021] A layer of dihydrochlorinated piperazine film is sprayed on the surface of the hole transport layer as a first interface modification layer.
[0022] A layer of Cs is deposited on the first interface modification layer by a scraping method. 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 The membrane layer serves as a power generation layer.
[0023] A layer of dihydrochlorinated piperazine film is sprayed on the surface of the power generation layer as a second interface modification layer.
[0024] A layer of 2-thiopheneethylamine chloride film is sprayed on the second interface modification layer as the third interface modification layer.
[0025] A carbon 60 film layer is deposited on the third interface modification layer by thermal evaporation as a first electron transport layer.
[0026] A 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline film layer is deposited on the first electron transport layer by a doctor blade coating method as a second electron transport layer.
[0027] A layer of indium-doped zinc oxide is deposited on the second electron transport layer as a conductive layer by magnetron sputtering.
[0028] A copper layer is deposited on the conductive layer by screen printing as a metal electrode layer.
[0029] Furthermore, a layer of Cs is deposited on the first interface modification layer by a scraping method. 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 The membrane layer serves as a power generation layer and includes:
[0030] Into a solution of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1, FAI / FABr / CsI / CsBr / PbI2 / PbBr2 in a molar ratio of 0.48:0.32:0.12:0.08:0.6:0.4 was added to obtain a first precursor solution;
[0031] Guanidine tetrafluoroborate was added to the first precursor solution, heated and stirred at 50° C. for 2 hours, and filtered using 0.22 um polytetrafluoroethylene to obtain a second precursor solution.
[0032] The second precursor solution is scraped onto the dihydrochlorinated piperazine film to form Cs 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 Membrane layer.
[0033] Yet another embodiment of the present invention provides a perovskite solar cell, comprising the above-mentioned perovskite solar cell structure.
[0034] Compared with the prior art, the embodiments of the present invention have the following advantages:
[0035] (1) The surface FA+ cations of the perovskite film are fixed by hydrogen bonds of piperazine. The nitrogen atoms in piperazine act as hydrogen bond donors. The interaction between hydrogen bonds and FA+ cations locks FA+ on the surface of the perovskite film and makes it difficult to fall off. Dihydrochlorinated piperazine can induce Cl- doping on the surface of the perovskite film and form strong coordination bonds with uncoordinated Pb2+ in the perovskite film, filling the defects of the surface octahedral cage and reducing its hindrance to charge migration, effectively constraining the FA+ cations of the perovskite film and alleviating the surface lattice stress.
[0036] (2) After using a dihydrochlorinated piperazine film to regulate the interface between the perovskite and carbon 60 films, enhancing charge transfer and inhibiting non-radiative recombination at the interface, a 2-thiopheneethylamine chloride film was used to further passivate the top surface of the perovskite film, achieving good energy band matching and reducing vacancy trap states, thereby further improving device performance;
[0037] (3) By doping NiO with Mg and Li to prepare a hole transport layer, the Fermi level of the film layer can be increased, the hole concentration of the hole transport layer can be increased, and the photoelectric conversion efficiency value can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 A schematic structural diagram of a perovskite solar cell structure provided by the present invention;
[0039] Figure 2 is a schematic structural diagram of a perovskite solar cell structure provided by one embodiment of the present invention;
[0040] Figure numerals: 1. conductive glass layer; 2. hole transport layer; 3. first interface modification layer; 4. power generation layer; 5. second interface modification layer; 6. third interface modification layer; 7. first electron transport layer; 8. second electron transport layer; 9. conductive layer; 10. metal electrode layer. DETAILED DESCRIPTION
[0041] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. The purpose of providing these embodiments is to make the disclosure of the present invention more thorough and comprehensive. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] In the description of this application, the terms "first", "second", "third", etc. are used for descriptive purposes only and are not to be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first", "second", "third", etc. may explicitly or implicitly include one or more of the feature. In the description of this application, unless otherwise specified, "plurality" means two or more.
[0043] In the description of the present application, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be a connection between the two elements. The terms "vertical", "horizontal", "left", "right", "upper", "lower" and similar expressions used herein are only for illustrative purposes, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items. For those of ordinary skill in the art, the specific meanings of the above terms in this application can be understood according to specific circumstances.
[0044] In the description of this application, it should be noted that, unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. For those of ordinary skill in the art, the specific meanings of the above terms in this application can be understood by specific circumstances.
[0045] An embodiment of the present invention provides a perovskite solar cell structure. For details, see Figure 1 and Figure 2 , Figure 1 A schematic diagram of a perovskite solar cell structure provided by the present invention is shown. Figure 2 A schematic structural diagram of a perovskite solar cell structure provided in one embodiment of the present invention is shown, comprising:
[0046] Arranged from bottom to top are a conductive glass layer 1, a hole transport layer 2, a first interface modification layer 3, a power generation layer 4, a second interface modification layer 5, a third interface modification layer 6, a first electron transport layer 7, a second electron transport layer 8, a conductive layer 9, and a metal electrode layer 10.
[0047] Specifically, Figure 1 and Figure 2 As shown:
[0048] The conductive glass layer 1 is disposed on one side of the hole transport layer 2 , and the first interface modification layer 3 is disposed on the side of the hole transport layer 2 away from the conductive glass layer 1 .
[0049] Due to the good light transmittance of conductive glass, solar energy can enter the solar cell and be converted into electrical energy, and conductive glass can effectively conduct electric current and improve the efficiency of solar energy. In a specific embodiment, using FTO (fluorine-doped tin oxide) as conductive glass can prevent reflection and damage on the surface of the solar panel and protect the components inside the component from damage.
[0050] In perovskite cells, the main function of the hole transport layer is to promote the transmission of photogenerated holes from the perovskite layer to the bottom electrode, thereby improving the conversion efficiency of the cell. Specifically, this embodiment uses NiMgLiO as the preparation material of the hole transport layer, and the thickness of the hole transport layer can be set to 20-30nm. By co-doping NiO with Li or Mg, the conductivity of the NiO hole transport layer can be significantly improved. This is conducive to the efficient migration of holes in the transport layer, reducing resistance losses, thereby improving the overall performance of the device, and by doping Mg and Li to increase the Fermi level of the film layer, the hole concentration of the hole transport layer is increased, and the photoelectric conversion efficiency value is improved.
[0051] One side of the power generation layer 4 is the first interface modification layer 3 , and the second interface modification layer 5 is disposed on the side of the power generation layer 4 away from the first interface modification layer 3 .
[0052] The power generation layer is the light absorption layer of the perovskite cell and is the core part of the entire cell. This embodiment uses a perovskite film layer as the power generation layer. Specifically, Cs 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 As the preparation material of the power generation layer, the thickness can be set to 300-500nm. In the design of the perovskite composition, a small amount of I defects and MA defects are the source of deep-level electron and hole defects in MAPbI3. Br doped in MAPbI3 has the effect of inhibiting hole defects. MA / FA / Cs can inhibit the appearance of yellow FAPbI3, which will lose the photoelectric effect. The introduction of MA and Cs can relax the stress of the crystal structure and stabilize the a-phase FAPbI3.
[0053] In the battery structure, the interface modification layer can reduce the energy level gap between the perovskite layer and the electron transport layer / hole transport layer, passivate interface defects, reduce the interface defect state density, reduce the recombination of carriers at the interface, and improve the carrier lifetime and transmission efficiency.
[0054] Specifically, this embodiment uses dihydrochlorinated piperazine (PDCl2) as the preparation material of the first interface modification layer and the second interface modification layer. The thickness of the first interface modification layer and the second interface modification layer can be set to 10-30 nm. Piperazine can fix the surface FA+ cations through hydrogen bonds. Through the formation of hydrogen bonds, piperazine can firmly lock FA+ on the surface of the perovskite film layer. The piperazine molecule contains two amino groups (-NH-) and nitrogen atoms. These nitrogen atoms can act as hydrogen bond donors and interact with FA+ cations in the perovskite film to fix FA+ cations. The formation of hydrogen bonds makes it difficult for FA+ cations to fall off, thereby improving the stability of the perovskite film layer.
[0055] In addition, during the production of the battery, the post-treatment of PDCl2 can induce Cl- doping on the surface of the perovskite film layer, forming strong coordination bonds with the uncoordinated Pb 2+ in the perovskite film layer. The formation of these coordination bonds can balance the octahedral PbX (where X is a halogen) structure. Among them, the coordination number of the lead ion is six, and the structure formed is called an octahedral structure. In this structure, six chloride ions are arranged around the lead ion in a vertex manner to form an octahedron, and Cl- acts on these defects through strong coordination, filling the defects of the surface octahedral cage and reducing its hindrance to charge migration. In this way, defects are reduced and surface integrity is improved. This synergy effectively constrains the FA+ cations of the perovskite film layer, relieves the surface lattice stress, and helps to improve the crystal quality of the film layer.
[0056] One side of the third interface modification layer 6 is the second interface modification layer 5 , and the first electron transport layer 7 is disposed on the side of the third interface modification layer 6 away from the second interface modification layer 5 .
[0057] The first interface modification layer 3 and the second interface modification layer 5 are respectively arranged on both sides of the power generation layer 4, and are used to fix the Pb2+ ions on the surface of the perovskite film layer to increase the stability of the perovskite film layer. In addition, a third interface modification layer 6 is required to be arranged between the second interface modification layer 5 and the first electron transport layer 7 to adjust the interface between the perovskite and the electron transport layer. Specifically, the third interface modification layer 6 in this embodiment is prepared by 2-thiopheneethylamine chloride (TEACl), and the film thickness is 10 to 20 nm, which is used to adjust the interface between the perovskite and the carbon 60 (C60) film layer, thereby enhancing charge transfer and inhibiting interface non-radiative recombination. After the perovskite film layer is modified by dihydrochlorinated piperazine, the top surface of the perovskite is further passivated by TEACl, thereby achieving good matching of energy bands, reducing vacancy trap states, and further improving device performance.
[0058] One side of the second electron transport layer 8 is the first electron transport layer 7 , and the side of the second electron transport layer 8 away from the first electron transport layer 7 is provided with the conductive layer 9 .
[0059] As a film layer that promotes electron transport in perovskite cells, the electron transport layer has excellent electron mobility and conductivity. It can effectively collect and transport photogenerated electrons generated by the perovskite layer, reduce the loss of electrons during the transmission process, thereby improving the photoelectric conversion efficiency and playing an important role in the realization of battery functions.
[0060] Specifically, the perovskite battery of this embodiment is provided with a first electron transport layer 7 and a second electron transport layer 8 to realize the transmission of electrons, wherein the first electron transport layer 7 can be a C60 film layer with a film thickness of 20 to 30 nm. The C60 film layer has a high electron mobility, which means that it can quickly transmit the photogenerated electrons generated by the perovskite layer to the external circuit, thereby reducing the loss of electrons during the transmission process. At the same time, the C60 film layer also has good conductivity, which can further reduce the resistance of the battery, increase the current output, and thus improve the photoelectric conversion efficiency of the battery.
[0061] The second electron transport layer 8 uses a 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) film layer with excellent electron transport performance, and the film thickness is 20 to 30 nm. At the same time, the BCP film layer is located between the perovskite film layer and the electrode. As a buffer layer between the perovskite film layer and the electrode, it isolates the direct erosion of the perovskite film layer by the external environment to a certain extent, thereby improving the stability of the battery.
[0062] The metal electrode layer 10 is disposed on a side of the conductive layer 9 away from the second electron transport layer 8 .
[0063] Specifically, the conductive layer 9 of this embodiment is made of indium-doped zinc oxide (ZnO:In), and the thickness of the conductive layer 9 can be set to 150-200 nm. The metal electrode layer 10 is made of copper (Cu), and the thickness of the metal electrode layer 10 can be set to 10-100 nm.
[0064] In summary, the present invention fixes the surface FA+ cations of the perovskite film layer through the hydrogen bonds of piperazine, and dihydrochlorinated piperazine can induce Cl- doping on the surface of the perovskite film layer, and form a strong coordination bond with the uncoordinated Pb2+ in the perovskite film layer to reduce the defects of the surface octahedral cage, effectively constrain the FA+ cations of the perovskite film layer, and relieve the surface lattice stress; after using the dihydrochlorinated piperazine film layer to adjust the interface between the perovskite and the carbon 60 film layer, enhance the charge transfer and inhibit the interface non-radiative recombination, the top surface of the perovskite film layer is further passivated using a 2-thiopheneethylamine chloride film layer, achieving good matching of the energy bands and reducing the vacancy trap state, thereby further improving the device performance; by doping Mg and Li, the Fermi level of the film layer is increased, the hole concentration of the hole transport layer is increased, and the photoelectric conversion efficiency value is improved.
[0065] The present invention also provides a method for preparing a perovskite solar cell, which specifically comprises the following steps:
[0066] S1. A NiMgLiO film is deposited on the conductive glass layer by magnetron sputtering as a hole transport layer.
[0067] A NiMgLiO layer is deposited on FTO conductive glass using magnetron sputtering method. The thickness of the NiMgLiO layer is 20-30nm. The film layer is used to transmit holes generated by the perovskite photovoltaic reaction. By doping Mg and Li, the Fermi level of the film layer is increased to better match the perovskite energy level, increase the hole concentration, and improve the PCE value.
[0068] S2, spraying a layer of dihydrochlorinated piperazine film on the surface of the hole transport layer as a first interface modification layer.
[0069] A layer of dihydrochlorinated piperazine (PDCl2) film with a thickness of 10-30 nm was sprayed on the surface of the NiMgLiO film. Piperazine can fix the surface FA+ cations through hydrogen bonds. In addition, post-treatment with PDCl2 can induce surface Cl– doping to form strong coordination bonds with uncoordinated Pb2+, thereby reducing the defects of the surface octahedral cage. This synergistic effect effectively constrains the surface FA+ cations while relieving the surface lattice stress. Due to the improved surface properties, the resulting perovskite not only exhibits excellent optical / thermal stability, but also shows more significant n-type characteristics and uniform potential distribution, thereby improving the charge transfer kinetics.
[0070] S3, depositing a layer of Cs on the first interface modification layer by a scraping method 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 The membrane layer serves as a power generation layer.
[0071] Specifically, the process of preparing the power generation layer includes:
[0072] S3.1. Prepare a mixed solution of N,N-dimethylformamide (DMF, chemical formula: C3H7NO) and dimethyl sulfoxide (DMSO, chemical formula: C2H6OS) in a volume ratio of 4:1.
[0073] FAI (formamidine hydroiodide, chemical formula CH5IN2), / FABr (formamidine hydrobromide, chemical formula CH5BrN2), CsI (cesium iodide), CsBr (cesium bromide), PbI2 (lead iodide), and PbBr2 (lead bromide) are added to the above mixed solution in a preset molar ratio. Specifically, the preset molar ratio can be 0.48:0.32:0.12:0.08:0.6:0.4.
[0074] S3.2. Add guanidine tetrafluoroborate (GuaBF4) to the mixed solution to improve the crystallinity of the perovskite film. Heat it at 50°C to accelerate the rate of the chemical reaction so that guanidine tetrafluoroborate reacts more fully with the components in the perovskite solution. Stir for 2 hours to evenly mix the reactants and ensure that the reactants are evenly distributed in the solution, thereby improving the reaction efficiency.
[0075] After completing the heating and stirring work, use 0.22um polytetrafluoroethylene (PTFE) to filter and remove impurities and insolubles produced during the reaction to obtain a relatively pure perovskite solution, providing conditions for the subsequent preparation of high-quality perovskite films.
[0076] S3.3, coating the second precursor solution on the dihydrochlorinated piperazine film layer to form Cs 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 The film layer has a thickness of 300 to 500 nm.
[0077] S4, spraying a layer of dihydrochlorinated piperazine film on the surface of the power generation layer as a second interface modification layer, with a film thickness of 10 to 30 nm.
[0078] S5. Spray a layer of 2-thiopheneethylamine chloride film on the second interface modification layer as a third interface modification layer, with a film thickness of 10 to 20 nm.
[0079] S6. Depositing a carbon 60 (C60) film layer as a first electron transport layer on the third interface modification layer by thermal evaporation, wherein the film layer has a thickness of 20 to 30 nm and is used to transport electrons generated by the perovskite photovoltaic reaction.
[0080] Specifically, the process of preparing the C60 film layer using the thermal evaporation method is as follows:
[0081] High-purity C60 powder is selected as the evaporation source material.
[0082] Ensure that the second interface modification layer and the third interface modification layer have been uniformly and stably deposited on the perovskite film layer, and the surface is clean and free of pollutants.
[0083] The battery base with a partial film layer prepared and the C60 powder are placed in a quartz crucible at the vacuum chamber and the evaporation source position respectively.
[0084] After the vacuum chamber is evacuated to a preset vacuum degree, the heating system is started to heat the evaporation source (i.e., the C60 powder in the quartz crucible) to a preset temperature until the C60 powder gradually evaporates to form gaseous molecules or atoms.
[0085] In a vacuum environment, gaseous C60 molecules or atoms move to the surface of the battery substrate, where they condense, nucleate, and grow, eventually forming a continuous C60 film.
[0086] After the C60 film is formed, the heating system is turned off and the vacuum chamber is allowed to cool naturally to room temperature, and the battery base with the C60 film layer prepared is taken out.
[0087] S7. Deposit a layer of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline (BCP) film as a second electron transport layer on the first electron transport layer by a scraping method. The film layer has a thickness of 20 to 30 nm and is used to transport electrons generated by the perovskite photovoltaic reaction.
[0088] S8. Depositing an indium-doped zinc oxide layer as a conductive layer on the second electron transport layer by magnetron sputtering, with a film thickness of 150 to 200 nm.
[0089] S9. Depositing a copper layer as a metal electrode layer on the conductive layer by screen printing, with a thickness of 10 to 100 nm.
[0090] In order to further clearly reflect the structural characteristics of the perovskite battery of the present invention, a perovskite solar cell structure, a preparation method and a battery provided by the present invention are described in detail below in combination with specific embodiments.
[0091] The reagents used in the following examples are all commercially available.
[0092] Embodiment 1:
[0093] (1) A NiMgLiO layer was deposited on the FTO conductive glass using a magnetron sputtering method. The NiMgLiO layer thickness was 25 nm.
[0094] (2) A layer of dihydrochlorinated piperazine (PDCl2) film is sprayed on the surface of the NiMgLiO film layer, and the film layer thickness is 20 nm.
[0095] (3) Deposit a layer of Cs by scraping 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 Perovskite film layer, film thickness is 400nm.
[0096] (3.1) Prepare the perovskite solution: Prepare the precursor solution in DMF (C3H7NO) and DMSO (C2H6OS) in a volume ratio of 4:1. Add the precursor solution with a molar ratio of FAI (CH5IN2) / FABr (CH5BrN2) / CsI / CsBr / PbI2 / PbBr2 of 0.48:0.32:0.12:0.08:0.6:0.4. Add GuaBF4 (guanidine tetrafluoroborate) to the precursor solution. Heat and stir the precursor solution at 50°C for 2 hours, and then filter it with 0.22um PTFE (polytetrafluoroethylene) before use.
[0097] (3.2) The filtered solution was scraped onto the PDCl2 film layer with a film thickness of 400 nm.
[0098] (4) In Cs 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 A layer of dihydropiperazine chloride (PDCl2) film is sprayed on the surface of the perovskite film layer, and the film layer thickness is 20nm.
[0099] (5) A layer of 2-thiopheneethylamine chloride (TEACl) film is sprayed on the dihydrochlorinated piperazine (PDCl2) film layer, and the film layer thickness is 15 nm.
[0100] (6) A C60 (carbon 60) film layer is deposited by thermal evaporation method, and the thickness of the C60 film layer is 25 nm.
[0101] (7) A layer of BCP (2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline) film is deposited by a scraping method with a film thickness of 25 nm.
[0102] (8) A ZnO:In layer is deposited by magnetron sputtering. The thickness of the ZnO:In layer is 150 nm.
[0103] (9) A Cu layer is deposited as an electrode using a screen printing method, and the Cu layer thickness is 50 nm.
[0104] Embodiment 2:
[0105] A perovskite battery was prepared according to the method of Example 1, except that:
[0106] The thickness of the PDCl2 film layer in step (2) and step (4) can be set to a combination of 5nm, 10nm, 30nm, 35nm or above, and the thickness of the remaining film layers are the same. The PDCl2 film layer with a thickness of 20nm is used as a comparative reference example to test the effects of the first interface optimization layer and the second interface optimization layer of different thicknesses on the photoelectric conversion efficiency.
[0107] Embodiment 3:
[0108] A perovskite battery was prepared according to the method of Example 1, except that:
[0109] The thickness of the TEACl film layer in step (5) can be set to 5nm, 10nm, 20nm, 30nm, and the thickness of the other film layers are the same. The TEACl film layer with a thickness of 15nm is used as a comparative reference example to test the effect of different thicknesses of the third interface optimization layer on the photoelectric conversion efficiency.
[0110] Embodiment 4:
[0111] The difference between this embodiment and embodiment 1 is that the perovskite film layer in this embodiment is MAPbI3 or FAPbI3, and the rest is the same.
[0112] Embodiment 5:
[0113] The present embodiment is different from the embodiment 1 in that the hole transport layer in the present embodiment is NiO, and the rest is the same.
[0114] Based on the preparation, observation and testing process of Example 1, Example 2, Example 3, Example 4 and Example 5, each example and comparison are shown in Table 1:
[0115] Table 1 Effects of different interface modification layer thickness, perovskite film material and hole transport layer material on the performance of perovskite cells
[0116]
[0117]
[0118] It can be seen from the results in Table 1 that the performance of the perovskite cell using the cell structure of the present invention is significantly better than the photoelectric conversion efficiency of the cell using FAPbI3 and MAPbI3 as the perovskite film layer and using NiO as the hole transport layer, and the photoelectric conversion efficiency of the cell within the thickness range of each interface modification layer set by the present invention is also significantly better than the photoelectric conversion efficiency of PDCl2 and TAECl at other thicknesses.
[0119] Another embodiment of the present invention provides a perovskite solar cell, comprising the above-mentioned perovskite solar cell structure. The perovskite solar cell of the present invention is provided with an interface modification layer made of dihydrochlorinated piperazine on the upper and lower sides of the perovskite film layer, which increases the stability of the battery and improves the conversion efficiency of the battery compared to the traditional perovskite battery.
[0120] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A perovskite solar cell structure, characterized in that: It includes a conductive glass layer, a hole transport layer, a first interface modification layer, a power generation layer, a second interface modification layer, a third interface modification layer, a first electron transport layer, a second electron transport layer, a conductive layer, and a metal electrode layer arranged in sequence from bottom to top; The conductive glass layer is disposed on one side of the hole transport layer, and the first interface modification layer is disposed on the side of the hole transport layer away from the conductive glass layer; One side of the power generation layer is the first interface modification layer, and the side of the power generation layer away from the first interface modification layer is provided with the second interface modification layer; One side of the third interface modification layer is the second interface modification layer, and the first electron transport layer is disposed on the side of the third interface modification layer away from the second interface modification layer; One side of the second electron transport layer is the first electron transport layer, and the side of the second electron transport layer away from the first electron transport layer is provided with the conductive layer; The metal electrode layer is provided on a side of the conductive layer away from the second electron transport layer; The first interface modification layer and the second interface modification layer are both prepared from dihydrochlorinated piperazine.
2. The perovskite solar cell structure according to claim 1, characterized in that: The thickness of the first interface modification layer and the second interface modification layer is 10-30 nm.
3. The perovskite solar cell structure according to claim 1, characterized in that: The power generation layer is composed of Cs 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 Prepared.
4. The perovskite solar cell structure according to claim 2, characterized in that: The thickness of the power generation layer is 300-500 nm.
5. The perovskite solar cell structure according to claim 1, characterized in that: The power generation layer is prepared from MAPbI3 or FAPbI3.
6. The perovskite solar cell structure according to claim 1, characterized in that: The third interface modification layer is prepared from 2-thiopheneethylamine chloride.
7. The perovskite solar cell structure according to claim 4, characterized in that: The thickness of the third interface modification layer is 10-30 nm.
8. A method for preparing a perovskite solar cell, characterized in that: The perovskite solar cell structure according to any one of claims 1 to 7 comprises: A NiMgLiO film is deposited on the conductive glass layer by magnetron sputtering as a hole transport layer; Spraying a layer of dihydrochlorinated piperazine film on the surface of the hole transport layer as a first interface modification layer; A layer of Cs is deposited on the first interface modification layer by a scraping method. 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 The membrane layer serves as a power generation layer; Spraying a layer of dihydrochlorinated piperazine film on the surface of the power generation layer as a second interface modification layer; Spraying a layer of 2-thiopheneethylamine chloride film on the second interface modification layer as a third interface modification layer; Depositing a carbon 60 film layer as a first electron transport layer on the third interface modification layer by thermal evaporation method; Depositing a layer of 2,9-dimethyl-4,7-diphenyl-1,10-phenanthroline film as a second electron transport layer on the first electron transport layer by a doctor blade coating method; Depositing an indium-doped zinc oxide layer as a conductive layer on the second electron transport layer by magnetron sputtering; A copper layer is deposited on the conductive layer by screen printing as a metal electrode layer.
9. The method for preparing a perovskite solar cell according to claim 8, characterized in that: The first interface modification layer is deposited by a scraping method. 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 The membrane layer serves as a power generation layer and includes: Into a solution of N,N-dimethylformamide and dimethyl sulfoxide in a volume ratio of 4:1, FAI / FABr / CsI / CsBr / PbI2 / PbBr2 in a molar ratio of 0.48:0.32:0.12:0.08:0.6:0.4 was added to obtain a first precursor solution; Adding guanidine tetrafluoroborate to the first precursor solution, heating and stirring at 50° C. for 2 hours, and filtering with 0.22 um polytetrafluoroethylene to obtain a second precursor solution; The second precursor solution is scraped onto the dihydrochlorinated piperazine film to form Cs 0.05 FA 0.67 MA 0.33 PbB 1.31 I 1.69 Membrane layer.
10. A perovskite solar cell, characterized in that: It comprises the perovskite solar cell structure as described in any one of claims 1 to 7.
Citation Information
Cited By
Large-area perovskite solar cell preparation method and system, and cell
CN121692956A
